THE CONCEPT OF THE SYSTEM OF LEGAL PROTECTION OF OBJECTS WILDLIFE AS A RESULT OF INTELLECTUAL ACTIVITY - Bessarab , Наталия Сергеевна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The problems of the legal regime of the results of creative activity related to wildlife and humans have acquired special scientific significance and practical value in many countries, including Russia and Kazakhstan. Therefore, research on the development of concepts for the adaptation of the intellectual property law system as a sub-branch of civil law, the definition of the legal regime of new wildlife objects resulting from intellectual activity, and their integration into the already existing legal system, have a strategic level of state tasks aimed at achieving a balance of public and private interests, especially in the field of biomedical technologies and genomic experiments that create very significant risks not only for the living humanity, but also for future generations. Taking into account the above, this article presents the results of a scientific analysis conducted in order to develop a theoretical concept for building a system of legal protection of wildlife objects as the results of intellectual activity and to make proposals for improving legislation in the field of intellectual property law. Based on the results of the study, it is proposed to modernize the system of law in the field of intellectual property in terms of objects of wildlife, including new objects in addition to existing breeding achievements, namely: strains of microorganisms, genetically modified organisms, biomedical cell products, genomes, and other results of intellectual activity created using human and animal biomaterials, including birds, fish and other representatives of fauna, and provide them with an independent legal regime. The revision of the last object "other results ..." allows you to leave the list of wildlife objects open in order, if necessary, to introduce another innovative object into the intellectual property system, providing it with an appropriate legal regime, without additional changes to the law.